THU0463 EXPECTATIONS OF TREATMENT RESULT OF KNEE OSTEOARTHRITIS PATIENTS TREATED WITH A TOTAL KNEE ARTHROPLASTY. THE INFLUENCE OF DEMOGRAPHIC FACTORS, PAIN, PERSONALITY TRAITS, PHYSICAL AND PSYCHOLOGICAL STATUS. (June 2019) - Tolk, J.J.; Janssen, R.P.A.; Haanstra, T.M.; van der Steen, M. (Marieke) C.; Bierma-Zeinstra, S.M.A.; Reijman, Max
Abstract : Background: Unrealistic preoperative expectations have a strong influence on the outcome after total knee arthroplasty (TKA). More insight into determinants of the level of expectations is useful in identifying patients at risk for unrealistic expectations. This information can be used in optimizing pre-operative expectation management. Objectives: The aim of the current study was to analyze to what extent pre-operative outcome expectations of TKA patients are determined by psychological factors, demographic factors, pain, physical function and general health status. Methods: A cross-sectional analysis of 204 patients with symptomatic and radiographic knee OA, scheduled for primary TKA was conducted. Outcome expectations were measured using the Hospital for Special Surgery knee replacement expectations survey. Independent variables included were age, sex, body mass index and patient reported outcome measures for pain, physical function, quality of life, anxiety, depression, catastrophizing, optimism and pessimism. Multiple linear regression analyses were used to evaluate associations between these variables and pre-operative outcome expectations Results: The mean overall survey score on the HSS-KRES was 70.9 (SD 17.9). Distribution of expectation scores is shown in Figure 1 . Highest expectations were scored for pain relief and improvement of the ability to walk of short and medium distances. Patients had the lowest expectations for improvement in kneeling, squatting, psychological well-being sexual activity and the ability to have paid work. Female sex, higher age, higher depression score and duration of complaints > 50 months showed to be significant predictors of lower expectations for the treatment outcome after TKA. Baseline pain and function scores were not related to the level of pre-operative expectations. Conclusion: In conclusion young, male patients with a short duration of complaints might be at risk of having too high expectations of the treatment result. On the contrary patients with depressive symptoms are more likely to have low expectations, with a potential negative influence on their treatment result. The present study aids in identifying patients at risk for having either too high or too low expectations. This knowledge can be utilized in individualized expectation management interventions. Acknowledgement: We would like to thank C. van Doesburg and H. Kox for their support in data collection and study procedures. Disclosure of Interests: None declared